Case report: Primary cytomegalovirus infection in a patient with late onset multiple sclerosis treated with dimethyl fumarate - Muñoz, Julia Sabin; Santiago, Alberto Díaz-De; Escudero, José Cebrián; Merino, J. A. García (Frontiers in Neurology, 2024)
Background: Treatment of multiple sclerosis (MS) with delayed-release dimethyl fumarate (DMF) has shown efficacy and safety in clinical trials. However, the occurrence of infectious complications, particularly in elderly patients, remains a concern. Methods: We present the case of a 63-year-old woman with late-onset MS treated with DMF, who developed a severe primary cytomegalovirus (CMV) infection. DMF was discontinued, and antiviral treatment was initiated, resulting in complete resolution of symptoms. Results: While DMF is generally considered safe in terms of opportunistic infections, this case highlights the possibility of serious infectious complications in eldery DMF-treated patients, even without documented lymphopenia. Conclusions: Advanced age and the associated immunological changes may contribute to an inadequate immune response to MS treatments, highlighting the importance of a careful treatment choice in elderly patients with MS. Further research and specific data on the safety and efficacy of DMF in this population are required to guide clinical decision-making.